1,2,3. - Wewerka & Weiss Galerie, Berlin (Berlin : Wewerka & Weiss Galerie, 1990)
Flieger, Albrecht ; Gries, Gero ; Jokl, Ivonne ; Munk, Bettina ; Heisterkamp, Fritz ; Hemmert, Hans ; Kunzmann, Thomas ; Zey, Georg ; Bayer, Knut ; Eichhorn, Maria ; Figura, Martin ; Kühn, Ulrich ; Schaerf, Eran
1,2,3, Wewerka & Weiss Galerie, Berlin, 20.10 - 23.11.1990 / 1.12. - 31.12.1990 / 5.1. - 25.1.1991
boek